Analyzing consumer behavior through organizational capabilities and digital technologies: the mediating role of proactive marketing - Kofar Naisa, Farouk Umar; Alhaji Sani, Armaya’u; Al-Absy, Mujeeb Saif Mohsen; Zahid, Umair; Pantamee, Abdurrahman Adamu; Bala, Hussaini (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
The study highlights the importance of proactive marketing, which links organizational resources and capabilities to influence consumer behavior. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) and data from 454 respondents, it was found that proactive marketing served as a mediating variable in aligning organizational resources and competencies with customer behavior. This research emphasized the significance of proactive marketing in leveraging organizational strengths to analyze and influence consumer behavior, informing strategic decisions and improving business performance. Future research may explore how proactive marketing strategies affect different organizational competencies and consumer segments, helping firms navigate the digital business landscape. The value of a company’s stock rises in tandem with its level of dynamic capability. Our understanding of user behavior, adaptability, and value to many businesses is greatly enhanced by these findings. The study theoretically enhanced existing literature by expanding the concept of dynamic capabilities to incorporate intelligence and information-processing abilities that are aligned with culture. The findings provide important insight in assisting the management in aligning technology adoption and integrating dynamic capabilities. Therefore, the research highlighted the need for managers to invest more in facilities that have dynamic capabilities.